A rare case of Epstein–Barr virus‐related plasmacytoma involving maxillary sinus mucosa. Issue 9 (26th July 2017) - Gibbs, Julie D.; Leon, Marino E.; Liu, Kenia; Nguyen, Johnny; Zhang, Ling
Key Clinical Message: Extramedullary plasmacytomas, Epstein–Bar virus (EBV) associated, are rarely encountered and usually have a fairly good clinical outcome. EBV+ plasmacytoma may cause a diagnostic dilemma as it phenotypically resembles an aggressive plasmablastic lymphoma (PBL). Herein, we report a unique case with maxillary EBV+ plasmacytoma from a 76‐year‐old immunocompetent individual. Abstract : Extramedullary plasmacytomas, Epstein–Bar virus (EBV) associated, are rarely encountered and usually have a fairly good clinical outcome. EBV+ plasmacytoma may cause a diagnostic dilemma as it phenotypically resemble to an aggressive plasmablastic lymphoma (PBL). Herein, we report a unique case with maxillary EBV+ plasmacytoma from a 76‐year‐old immunocompetent individual.